Representation of National Minorities in State Institutions Through Quotas in The Region of South East Europe - HAXHIU, Sadik; HAMITI, Urtak; ASLLANI, Gani (Journal of Advanced Research in Law and Economics; Vol 9 No 1 (2018): JARLE Volume IX Issue 1(31) Spring 2018, 2018)
Modern democratic societies and countries that are based on democracy, rule of law, respect of human rights and freedoms base those values in electoral systems and free and fair elections that legitimize the power of the people through their representatives. Norms for democratic electoral systems were set by various international institutions such as United Nations, Council of Europe, Organization for Security and Cooperation in Europe, and European Union. Although not all of the countries of the region of South East Europe are members of most relevant international institutions, they have adopted democratic norms concerning elections that are set by international institutions. Representation of national minorities in state institutions, legislative and executive branches, as well as other public institutions, through electoral systems or through constitutional and legal quotas, in some cases based on electoral systems or through political appointments, is the key ingredient of a full-functioning democratic order. This is even more important in the countries of South East Europe, many of which have been established in recent history, where the boundaries are geographic and are not set along ethnic lines. Most of the countries, regardless of the democratic elections, have opted for the system of quotas for their national minorities, in terms of their representation in state and public institutions, with the sole aim of bringing them on-board with the representatives of national majority to create democratic governing decision-making bodies.